2001
DOI: 10.1116/1.1418398
|View full text |Cite
|
Sign up to set email alerts
|

Focus latitude enhancement of symmetrical phase mask design for deep submicron contact hole patterning

Abstract: The mechanism of focus latitude enhancement for contact/via hole printing is explained by approximating the axis intensity distribution of an image as a series of cosine functions to characterize the interference between each pair of diffraction beams. It is found that a phase-shifting mask ͑PSM͒ with symmetrical assist features improves the depth of focus ͑DOF͒ by introducing destructive interference to counterbalance the intensity fluctuation from constructive interference as defocus. A simple formula was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…10 The prototype of customized illumination aperture filter (CIF) for contact hole patterning. vious work, 25 we have demonstrated a higher degree of illumination incoherence can alleviate this anomalous defocus behavior at the cost of DOF degradation. In the CIF design, we can control the degree of partial coherence through adjusting the quadruple width q to balance the performance between focus shift suppression and DOF enhancement.…”
Section: Experimental Conditionsmentioning
confidence: 96%
See 1 more Smart Citation
“…10 The prototype of customized illumination aperture filter (CIF) for contact hole patterning. vious work, 25 we have demonstrated a higher degree of illumination incoherence can alleviate this anomalous defocus behavior at the cost of DOF degradation. In the CIF design, we can control the degree of partial coherence through adjusting the quadruple width q to balance the performance between focus shift suppression and DOF enhancement.…”
Section: Experimental Conditionsmentioning
confidence: 96%
“…6͔. In our previous work, 25 we have shown that the DOF enhancement of the phase-shifting method comes from the destructive interference between the negative and positive mask frequencies to counterbalance the axis intensity variation as defocus. Increasing the degree of partial coherence degrades the focal range enlargement because a larger illumination angle elongates the destructive interference pattern in optical-axis direction so that its ability for intensity compensation is weakened.…”
Section: Sparse Hole Patternsmentioning
confidence: 98%
“…A mandatory step to further optimise the photolithographic process is the understanding of the optical phenomena in the pupil plane. Several papers have shown [5][6][7] that the optimal depth of focus (DOF) is reached when the beams captured by the pupil are symmetrical to the optical axis. This means that the shape of the beams incident onto the mask impact the distribution of the diffraction orders in the pupil plane.…”
Section: Introductionmentioning
confidence: 99%
“…The shape and the position of these beams in the pupil plane have a great impact on the lithographic performance: if two beams are symmetrical to the optical axis, the DOF is at maximum [5,6] (Fig. 1b).…”
mentioning
confidence: 99%